Analysis of the Role of Social Entrepreneurs Broadcasting Institutions towards Sustainable Smart City through Value Added and Citizen Journalism - Yani, Ahmad; Evasai, Aprilia Dian (Formosa Journal of Science and Technology, 2023)
Social entrepreneurship is an institution that not only operates in the social sector, but is also an institution that tries to gain profit from its business. Radio Andika as a broadcasting institution organized these two activities. On the one hand, this institution carries out profit activities, namely from various income obtained through advertisements, on the other hand, this institution also carries out social activities such as Friday Blessings, Friends of the Dhuafa, Caring for Orphans and various other social activities. This research aims to determine the influence of broadcasting institutions' social entrepreneurship on smart city sustainability with value added and citizenship journalism as mediating variables. The research results show that the social entrepreneur variable has no direct effect on the sustainability of smart cities; the value added variable cannot mediate the influence of social entrepreneurship on smart city sustainability; The citizenship journalism variable can mediate the influence of social entrepreneurship on the sustainability of smart cities.